Factors Associated with Interstitial Lung Disease in Patients with Polymyositis and Dermatomyositis: A Systematic Review and Meta-Analysis. - Li Zhang; Guoqin Wu; Di Gao; Guijian Liu; Lin Pan; Liyan Ni; Zheng Li; Qiang Wang (PLoS ONE, 2016)
Objectives Interstitial lung disease (ILD) is an extramuscular manifestation that results in increased morbidity and mortality from polymyositis (PM) and dermatomyositis (DM). The aim of this study was to systematically evaluate risk factors associated with the development of ILD in PM/DM. Methods Observational studies were identified from searching PubMed, Medline, Embase, and the Cochrane Library. Pooled odds ratios (ORs) or standardized mean differences (SMDs) and corresponding 95% confidence intervals (CIs) were obtained for the relationships between risk factors and ILD in PM/DM using either fixed- or random-effects models, whichever were appropriate. Heterogeneity tests, sensitivity analyses, and publication bias assessments were also performed. Results Twenty-three studies were selected for a meta-analysis that included 834 patients and 1245 control subjects. Risk factors that may have increased the risk of developing ILD in PM/DM patients included older age at diagnosis (SMD, 0.35; 95% CI, 0.18-0.52; P < 0.0001), arthritis/arthralgia (OR, 3.17; 95% CI, 1.99-5.04; P < 0.00001), fever (OR, 2.31; 95% CI, 1.42-3.76; P = 0.0007), presence of anti-Jo-1 antibodies (OR, 3.34; 95% CI, 2.16-5.16; P < 0.00001), elevated erythrocyte sedimentation rate (ESR; SMD, 0.48; 95% CI, 0.32-0.64; P < 0.00001), presence of anti-MDA5 antibodies (OR, 18.26; 95% CI, 9.66-34.51; P < 0.00001), and elevated C-reactive protein level (CRP; OR, 3.50; 95% CI, 1.48-8.28; P = 0.004). Meanwhile, malignancy (OR, 0.36; 95% CI, 0.18-0.72; P = 0.004) reduced the risk of developing ILD in PM/DM patients. Conclusion Our meta-analysis results suggest that the association between PM/DM and ILD may be due to such risk factors as older age at diagnosis, arthritis/arthralgia, fever, presence of anti-Jo-1 antibodies, elevated ESR, presence of anti-MDA5 antibodies, and elevated CRP level, while malignancy was associated with a reduced risk of developing ILD. Thus, these variables may be used to guide screening processes for ILD in patients with PM/DM.